2019
DOI: 10.3390/app9173521
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different District Integration for a Distributed Generation System for Heating and Cooling in an Urban Area

Abstract: The paper proposes a comparison of different district integration options for a distributed generation system for heating and cooling in an urban area. The system considered includes several production units located close to the users, a central unit and the district heating and cooling network which can connect all the users to each other and to a central unit, where a cogeneration system and a solar plant can be placed. Thus, each user can be regarded as isolated from the others, satisfying its energy needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Therefore, the study highlights the potential heat sources and the match with the small and medium size, low temperature CCHP technologies that will be still of interest, even in a future scenario dominated by RE resources and massive electrification, showing that reductions in the LCOE and LCOH can be achieved through a wider integration of the thermal products. Full exploitation of the potential benefit of CHP could be reached only by means of an optimization procedure of CHP units, jointly with the DH local grids [145,146], in the considered economic and energy-demand scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study highlights the potential heat sources and the match with the small and medium size, low temperature CCHP technologies that will be still of interest, even in a future scenario dominated by RE resources and massive electrification, showing that reductions in the LCOE and LCOH can be achieved through a wider integration of the thermal products. Full exploitation of the potential benefit of CHP could be reached only by means of an optimization procedure of CHP units, jointly with the DH local grids [145,146], in the considered economic and energy-demand scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The case they studied in Northern Italy demonstrated how the storage operation could allow solar energy to cover total demand. Solar thermal energy integration has also been studied in an industrial sector [28,29] using MILP approaches. This showed that, in a combined heat and power (CHP) system, the optimized solar field produced around 55% of user annual demand.…”
Section: Optimization Issues Of State-of-the-art District Heating Network and Tools Used To Address The Problemmentioning
confidence: 99%
“…The storage is therefore broken down into 91.25 small equal volumes called V part , and we assume that storage use on one of the typical days is the same as for the other 91.25 times. The terms V hot and V cold from Equations ( 26)- (29) become V hot,part and V cold,part with V hot,part + V cold,part = V part and V total = 91.25 × V part . According to Equations ( 26)- (29), when moving from one typical day to another (i.e., from one season to another) the state of the storage at the end of a season is retained at the start of the next.…”
Section: Storage Modelmentioning
confidence: 99%
See 2 more Smart Citations